Effect of Mo on the High-Temperature Creep Resistance and Machinability of a Recycled Al-Alloy with High Iron Impurity - Wan Qurratul Ain, Wan Mohamad; M. K., Faisal; M. K., Talari; W., Darham; M. M., Ratnam; Y., Kwon; N. J., Kim; A. K., Prasada Rao (Springer US, 2016)
Reported work focuses on the effect of morphology of the Fe-rich intermetallic phases on the machinability of Al-alloy containing >2wt.% Fe, obtained from automotive scrap. Effect of Mo addition on the microstructure, high-temperature impression creep and thereby the machinability of the Al-recycled alloy were studied. The machinability of the recycled alloy was estimated by investigating the built-up-edge (BUE) and surface roughness (Ra). SEM-EDS and TEM-SADP studies have shown that the crystal structure (BCC) of the Al8Fe2Si phase remained unchanged; however, Mo replaced few Fe atoms with little effect on the lattice dimension. It has been found that the addition of Mo to the recycled alloy suppresses the formation of β-phase (Al5FeSi) by suppressing the peritectic transformation of α (Al8Fe2Si) phase. Such suppression is found to improve the high-temperature creep resistance and the machinability with the increase in the Mo addition level.